Average blood Heme Oxygenase-1 (HO-1) levels in non silica exposure people, Prayao Province - ด่านไพบูลย์ อนงค์ศิลป์; หลิวเสรี วิทยา; ชัยสุวรรณ ชาญณรงค์; ขันติพงศ์ เจียรนัย; คชาอนันต์ ศุภกิจ; นามบุญมี โกวิทย์ (Disease Control Journal, 2018)
This cross sectional study aimed to determine the average of Blood Heme Oxygenase-1 (HO-1) levels on non silica exposed people at Phayao province, Thailand. Forty hundred and ten of non silica exposure cases were randomly recruited from people over 18 years of age and living in the area which is unexposed to silica dust at Phayao province. The results showed the average of Blood HO-1 level in mean on men and women was 26.34 ng/ml and 21.93 ng/ml, respectively. The cases who are 41-50 years old had highest levels of HO-1 level (31.34 ng/ml) and the cases were students had the highest average of HO-1 level (34.47 ng/ml), respectively. Also the difference of median (inter quartile range) of HO-1 levels by sex, age, occupation, smoking, alcohol consumption were not statistically significant (p<0.05). However this study was conducted on normal cases, therefore, the study on silicosis patients must be researched and determine the specificity of HO-1 analysis to improve the early silicosis screening.